2011
DOI: 10.1117/1.3652708
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of optical coherence tomography for the detection of epithelial cancers in vitro

Abstract: Abstract. Optical coherence tomography (OCT) is a noninvasive imaging methodology that is able to image tissue to depths of over 1 mm. Many epithelial conditions, such as melanoma and oral cancers, require an invasive biopsy for diagnosis. A noninvasive, real-time, point of care method of imaging depth-resolved epithelial structure could greatly improve early diagnosis and long-term monitoring in patients. Here, we have used tissue-engineered (TE) models of normal skin and oral mucosa to generate models of mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…A rhodamine 6G-based initiator prepared in-house (83.8 mg, 0.135 mmol) was dissolved in methanol (0.75 ml) and added to the MPC. The solution was deoxygenated by bubbling N2 for 30 10 mmol) and methanol (2 ml) was injected into the flask and 48 h later the reaction solution was diluted with methanol (~70 ml) and opened to the atmosphere. When the suspension turned green, 200 ml chloroform was added to dissolve the copolymer and the solution passed through a silica column to remove the catalyst.…”
Section: Rhodamine (Rho)-pmpc30pdpa60 Copolymer Synthesismentioning
confidence: 99%
“…A rhodamine 6G-based initiator prepared in-house (83.8 mg, 0.135 mmol) was dissolved in methanol (0.75 ml) and added to the MPC. The solution was deoxygenated by bubbling N2 for 30 10 mmol) and methanol (2 ml) was injected into the flask and 48 h later the reaction solution was diluted with methanol (~70 ml) and opened to the atmosphere. When the suspension turned green, 200 ml chloroform was added to dissolve the copolymer and the solution passed through a silica column to remove the catalyst.…”
Section: Rhodamine (Rho)-pmpc30pdpa60 Copolymer Synthesismentioning
confidence: 99%
“…OCT was used for monitoring non-surgical treatment (imiquimod) of lentigo maligna. [43][44][45] The results of these studies showed a good correlation between OCT and pathology. In OCT melanoma is characterized by marked architectural disarray and presence of vertical, icicle-shaped structures.…”
Section: Optical Coherence Tomographymentioning
confidence: 68%
“…There is a similar need to provide an oral mucosa substitute, suitable for reconstructing primary or secondary oral mucosal defects due to limited viable donor-derived oral mucosal soft tissues. An ex vivo-produced oral mucosa equivalent has been successfully constructed and used for reconstruction of oral mucosal defects derived from oncologic resection, vestibuloplasty, and periodontal therapy [149,150,151]. An MC/chitosan composite scaffold was fabricated using isolated tilapia scale collagen via the process of lyophilization and dehydrothermal cross-linking at 130 °C in vacuo for use as a tissue engineered oral mucosa equivalent [152].…”
Section: Biomedical Applicationsmentioning
confidence: 99%